A real-time regional assimilation system of multi-source data of microwave temperature sounder onboard polar-orbiting satellites - Xi Shuang; Yu Tianlei; Ren Suling; Zhang Liyang; Tang Shihao (Dianzi Jishu Yingyong, 2024)
A real-time assimilation was realized, based on the meso-scale numerical prediction model WRF and WRFDA assimilation system，for data of microwave temperature sounder onboard polar-orbiting satellites, along with preliminary evaluation and application of the assimilation products. The results of assimilation experiments in 2018 show that: the standard deviations of O-B (the differences between observations and the forward radiative transfer model simulations of background) of channels 5~9 of AMSU-A data are reduced effectively. After assimilation, the standard deviations of O-A (the differences between observations and the forward radiative transfer model simulations of analysis) for each channel are also decreased. The application results of the outputs of assimilation and forecast are satisfactory on heavy rain and severe convection cases and typhoon cases.